Pemberdayaan Ibu Rumah Tangga Perumahan Bukit Mekarwangi Kota Bogor Pada Masa Pandemi Covid-19 Melalui Program Pelatihan Hidroponik - Rahmawati, Fani Nanda; Alfalathi, Siti Aminah (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2021)
Hydroponics has the concept that water is the main ingredient as a substitute for soil to fulfill nutrients in plants. The purpose of empowering housewives is to help overcome food security and reduce kitchen budgets for housewives in Bukit Mekarwangi Housing, Bogor City cereal sub-district during the Covid-19 Pandemic through hydroponic cultivation training so as to gain new insights and farming skills. With the existence of hydroponic cultivation to produce organic plants as food security during the Covid19 period. This training program uses lecture, demonstration and discussion methods. Implementation in this activity includes planning, implementation, and evaluation. The results of the training program indicated that the group of housewives at Bukit Mekarwangi Housing and its surroundings had begun to understand vegetable hydroponic techniques, from equipment preparation, planting to harvesting. The expected impact of these activities is awareness in managing narrow land and utilizing existing tools in the house and making valuable results. So that later they can produce vegetables through hydroponic techniques as a source of food security and also family economic income.